A Philippine 'coolie trade': Trade and exploitation of Chinese labour in Spanish colonial Philippines, 1850–98. (September 2020) - Ginés-Blasi, Mònica
Abstract : Chinese immigration to the Philippines has traditionally been studied in relation to commercial activities. But between 1850 and 1898, there was an unparalleled influx of Chinese labourers, which raised the number of Chinese residents to 100, 000. This influx was fuelled by the abundant profits obtained by Chinese brokers and foremen, Spanish institutions and authorities in Manila, consuls in China, and Spanish and British ship captains, all of whom extracted excessive fees and taxes from the labourers. The trade in and the exploitation of Chinese labourers in the Philippines have yet to be thoroughly researched. This article shows that the import and abuse of Chinese labourers in and to the Philippines continued throughout the second half of the nineteenth century, and that, despite some anti-Chinese Spanish colonial rhetoric, a wide range of actors and institutions, both in China and in the Philippines, took advantage of this unprecedented inflow of immigrants.